AIDS-related stigma in Thailand - Hasan, Md. Kamrul (© 2012 SAGE Publications, 2016)
This article was published in the Millennial Asia journal [© 2012 SAGE publications] and the definite version is available at : http://dx.doi.org/10.1177/097639961200300204 The article website is at: http://mla.sagepub.com/content/3/2/187.abstract